(untitled) (Revista Iberoamericana de Bioética, 2020)
The fight against food insecurity (FI) is one of the targets of the second Sustainable Development Goal: zero hunger and sustainable agriculture. This study sought to assess the food security of beneficiaries of a Brazilian income transfer programme, from the perspective of the Bioethics of Protection. The Brazilian Food Insecurity Scale was used to assess FI and applied to 298 female beneficiaries of an income transfer programme. The results revealed that 58.1% (n=173) had mild FI, 16.4% (n=49) moderate FI, and 8.1% (n=24) severe FI. The data proves that beneficiaries have alarming rates of FI and that there is an urgent need for solutions that mitigate the vulnerabilities to which these families are exposed.